2003
DOI: 10.1111/j.0014-3820.2003.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Virulence in a Plant Virus

Abstract: The evolution of virulence is a rapidly growing field of research, but few reports deal with the evolution of virulence in natural populations of parasites. We present here an observational and experimental analysis of the evolution of virulence of the plant virus Cucumber mosaic virus (CMV) during an epidemic on tomato in eastern Spain. Three types of CMV isolates were found that caused in tomato plants either a systemic necrosis (N isolates), stunting and a severe reduction of leaf lamina (Y isolates), or st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 52 publications
3
26
0
1
Order By: Relevance
“…For instance, it has been shown that when Barley stripe mosaic virus evolved by serial horizontal transfers, its virulence increased with no concomitant increase in the viral load (45). Despite having radically different levels of virulence, necrogenic and nonnecrogenic variants of Cucumber mosaic virus did not differ in their accumulation levels in tomato (20,21). Finally, in a recent study, a lack of correlation between fitness and virulence was also reported for foot-and-mouth disease virus (26).…”
Section: Discussionmentioning
confidence: 95%
“…For instance, it has been shown that when Barley stripe mosaic virus evolved by serial horizontal transfers, its virulence increased with no concomitant increase in the viral load (45). Despite having radically different levels of virulence, necrogenic and nonnecrogenic variants of Cucumber mosaic virus did not differ in their accumulation levels in tomato (20,21). Finally, in a recent study, a lack of correlation between fitness and virulence was also reported for foot-and-mouth disease virus (26).…”
Section: Discussionmentioning
confidence: 95%
“…Aunque diversos modelos teóricos de evolución de la virulencia han asumido una correlación positiva entre el nivel de multiplicación del patógeno y sus efectos en el huésped (Sacristán et al, 2005) y dicha correlación ha sido observada en algunos sistemas virus-planta (Heijbroek et al, 1999;Fargette et al, 2002;Martín et al, 2005), en otros casos se ha encontrado que virulencia y carga viral no estaban relacionados o incluso se correlacionaban negativamente (Rodríguez-Cerezo et al, 1991;Shi et al, 2002;Escriu et al, 2003;Sacristán et al, 2005;Pagán et al, 2007). El presente estudio es el primero en identificar una ausencia de correlación entre virulencia y carga viral en un closterovirus y en un huésped leñoso.…”
Section: Discussionunclassified
“…Therefore, all else being equal, in a natural situation it may be costly for the virus to harm its plant host. To test this prediction, Escriu et al (2003) performed field and laboratory studies seeking to understand the evolution of virulence (for example, reduction in lifespan biomass) and epidemiology of different CMV strains. The data gathered by these authors support the predicted negative correlation between virulence and the rate of transmission (Figure 3c: partial correlation coefficient controlling for strain type: r ¼ À0.96, d.f.…”
Section: Mode Of Transmission and Virulencementioning
confidence: 99%